Policing Intimate Partner Violence in the Witbank Policing Area - Phahlamohlaka, Robert; Khosa, Dorcas; Mofokeng, Jacob Tseko; Obioha, Emeka (International Journal of Criminology and Sociology, 2021)
In South Africa, like elsewhere, DV affects people regardless of class, age, ethnicity, or other attributes. Using data from a sample of 30 participants comprising of police officials and victims of DV from the Witbank policing area, this article sought to: determine how policing is being conducted on DV challenges, determine how DV cases are handled by the police and investigate the challenges faced by the police in DV related cases. Semi-structured interviews and the analysis of case dockets were utilized as a means of collecting information. The findings indicated that the overall police response to victims of DV is not good enough and the local police needs to take decisive action to rectify this. Based on the research findings, the recommendations are suggested to guide the police officials at the station on how to respond adequately.